Clinical Features, Diagnostic Test Performance, and Prognosis in Different Subtypes of Chronic Pulmonary Aspergillosis - Zhong, Huanhuan; Wang, Yaru; Gu, Yu; Ni, Yueyan; Wang, Yu; Shen, Kunlu; Shi, Yi; Su, Xin (Frontiers in Medicine, 2022)
Objective: The aim of this study was to describe clinical features in different subtypes of Chronic Pulmonary Aspergillosis (CPA)-Simple aspergilloma (SA), Chronic cavitary pulmonary aspergillosis (CCPA), Chronic fibrosing pulmonary aspergillosis (CFPA), Aspergillus nodule (AN) and Subacute invasive aspergillosis (SAIA), respectively, and identify long-term prognosis of CPA. Methods: We reviewed patients diagnosed with different subtypes of CPA from 2002 to 2020 at Nanjing Jinling Hospital, China. We analyzed the clinical and survival information of five different subgroups. A cox regression model was used to explore proper antifungal duration and long-term survival factors of CCPA and SAIA. Results: A total of 147 patients with CPA were included, consisting of 11 SA, 48 CCPA, 5 CFPA, 12 AN, and 71 SAIA. The most common underlying pulmonary disease was pulmonary tuberculosis (n=49, 33%), followed by bronchiectasis (n=46, 31.3%) and chronic obstructive pulmonary disease (COPD) or emphysema (n=45, 30.6%), while in SAIA and CFPA group, the most common was COPD or emphysema (45.1% and 100%). Cough (85%), expectoration (70.7%), hemoptysis (54.4%) and fever (29.9%) were common symptoms especially in CCPA, CFPA and SAIA group. The common imaging manifestations included cavitation (n=94, 63.9%), fungal ball (n=54, 36.7%), pleural thickening (n=47, 32.0%) and bronchiectasis (n=46, 31.3%). SAIA and CFPA group had lower value of hemoglobin (HB) and serum albumin (ALB) with higher C-reactive protein (CRP) and erythrocyte sedimentation rate (ESR). The positive rate of sputum culture, serum galactomannan (GM) and BALF GM was 32.7% (36/110), 18.4% (18/98) and 48.7% (19/39), respectively. SAIA, old age, male, low BMI, COPD or emphysema, multiple distribution, low serum ALB and positive sputum culture were adverse prognosis factors for SAIA and CCPA group, and BMI20.0 kg/m2 was independently associated with increased mortality (HR 5.311, 95%CI 1.405-20.068, p=0.014). Multivariable Cox regression indicated that surgery (HR 0.093, 95%CI 0.011-0.814, P=0.032) and antifungal duration >6 months (HR 0.204, 95%CI 0.060-0.696 P=0.011) were related to improved survival. Conclusion: The clinical features and laboratory test performance are different among SA, CCPA, CFPA, AN and SAIA. Low BMI was independent risk factor for survival. Selective surgery and antifungal duration over 6 months were associated with improved survival.